Effects of the compound extracts of Caprifoliaceae and Scutellaria baicalensis Georgi on the intestinal microbiota and antioxidant function - Zhang, Shunfen; Lv, Huiyuan; Cai, Xueying; Tang, Shanlong; Zhong, Ruqing; Chen, Liang; Zhang, Hongfu (Frontiers in Microbiology, 2024)
Caprifoliaceae and Scutellaria baicalensis Georgi are used in traditional Chinese medicine to clear heat and detoxify, and treat wind-heat colds, upper respiratory tract infections, and pneumonia in the Chinese encyclopedia ‘Ben Cao Gang Mu’ (AD 1552–1578). But the mechanism and the effects of the compound extract of Caprifoliaceae and Scutellaria baicalensis Georgi on intestinal health remain unclear. This study evaluated the antioxidant, anti-inflammatory, and intestinal protective functions of Caprifoliaceae and Scutellaria baicalensis Georgi from the perspective of intestinal microbes. Mice received diets with or without Caprifoliaceae and Scutellaria baicalensis Georgi extractive (BCA) for 2 weeks in this study. Results showed that BCA increased body weight gain, feed intake, and catalase (CAT) content of the mice, but reduced γ-glutamy transpeptidase (γ-GT) content in serum (p < 0.05). For colon microbiota, BCA increased Sobs, Chao, and Ace index, Campilobacterota, Patercibacteria, and Desulfbacterota abundance, but reduced Firmicutes phyla (p < 0.05). In genus level, BCA enhance Candidatus_Saccharimonas, Helicobacter, unclassified_f_Lachnospiraceae, Alistipes, norank_f_norank_o_Clostridia_vadinBB60_group, norank_f_Ruminococcaceae, unclassified_f_Ruminococcaceae, etc. abundance (p < 0.05), but significantly reduced Lactobacillus and Lachnospiraceae_UCG_001 abundance (p < 0.05). Moreover, BCA improved the concentration of acetic acid, butyric acid, propionic acid, valeric acid, and isovaleric acid, and diminished the concentration of isobutyric acid (p < 0.05). Correlation analysis shows that the changes in short-chain fatty acids and antioxidant and inflammatory indexes in serum were significantly correlated with BCA-enriched microbiota. This study supplemented a database for the application of Caprifoliaceae and Scutellaria baicalensis Georgi in clinical and animal production.